CHARACTER EDUCATION PRACTICE IN ENGLISH LEARNING TO THE STUDENTS OF SMA NEGERI 4 DENPASAR: PENERAPAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA INGGRIS PADA SISWA SMA NEGERI 4 DENPASAR - Sukraningsih, Gusti Ayu Gede; Sueni, Ni Made (Suluh Pendidikan : Jurnal Ilmu-Ilmu Pendidikan, 2019)
Character is a very basic element in human life. The increasing number of moralcrises in human life indicates the re?ection of moral values declining. Considering the importance of the character role, the government through Kemendikbud implements character education through the learning process. This research aimed at ?nding out the character education practice in English learning to the students of SMA Negeri 4 Denpasar. The method used in this research was descriptive qualitative research method. The data were collected by using the techniques of observation, deep interview, and document study. The data analysiswere conducted with qualitative data analysis which consist of data reduction, data display, conclusion, and veri?cation.Based on the analysis, it was found that (1) There were ?ve components in emotional intelligence including self-awareness, self-regulation, self-motivation, empathy, and developing relationship; (2) Spiritual Quotient (SQ) was the intelligent which were able to function Intelligent Quotient(IQ) and Emotional Quotient (EQ) effectively; and (3) approaches used by the teacher towards character education in English learning were providing the opportunity and ?exibility to the attitude of students to express the attitudes freely based on the stimulus received, encouraging learner readiness on the stimulus received, leading the students to a higher intellectual in solving problems, encouraging and directing learners to search the meaning of moral values,and directing students to implement moral values in life manner. The conclusion of this research is the balance among the practice of Spiritual Quotient (SQ) and Emotional Quotient (EQ) in the process of English learning to the students of SMA Negeri 4 Denpasar.